2016
DOI: 10.7287/peerj.preprints.1733
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gender differences and bias in open source: Pull request acceptance of women versus men

Abstract: Biases against women in the workplace have been documented in a variety of studies. This paper presents the largest study to date on gender bias, where we compare acceptance rates of contributions from men versus women in an open source software community. Surprisingly, our results show that women's contributions tend to be accepted more often than men's. However, women's acceptance rates are higher only when they are not identifiable as women. Our results suggest that although women on GitHub may be more comp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(84 citation statements)
references
References 3 publications
4
77
2
1
Order By: Relevance
“…The observed results of overall bias with some outliers towards more significant bias against women are logical, as they describe a similar picture as [9], enriching these results with a higher precision on a project level and showing outliers on this level of detail. Further qualitative research should now be able to investigate a small number of specific projects and determine why they are more biased than others and compare the results with those that do not exhibit bias, such as the "rails" and "kubernetes" projects.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The observed results of overall bias with some outliers towards more significant bias against women are logical, as they describe a similar picture as [9], enriching these results with a higher precision on a project level and showing outliers on this level of detail. Further qualitative research should now be able to investigate a small number of specific projects and determine why they are more biased than others and compare the results with those that do not exhibit bias, such as the "rails" and "kubernetes" projects.…”
Section: Resultssupporting
confidence: 70%
“…Lastly, the study has investigated simply the correlation between gender and merge rate, it does not infer the cause of the PR merge decision outcome to be the gender. The literature does suggest the average female contribution be of better quality than that of a male possibly due to the survivorship bias observed with female software developers [9].…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…In OSS in general and GITHUB in particular, sociodemographic diversity is lower than anywhere else in tech [39]. Women are particularly underrepresented, with recent surveys placing them at less than 5% [40]; women are also more likely than men to encounter stereotyping or unwelcoming language [41]- [43]. However, as prior results from the film industry, a similarly male-dominated field, show, women can overcome the negative effects of network closure: being more often attached to open teams with regard to diversity of ties, information flow, and genre background increases chances of career survival [22].…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…Discrimination exists in online software engineering communities and women are known to face greater barriers than men [45]. Terrell et al show that women whose gender identities are revealed have lower pull request acceptance rate [43]. Mendez et al have observed biases against women in GITHUB tools and infrastructure [23], while Ford et al identified barriers for female participation on Stack Overflow [46].…”
Section: Related Workmentioning
confidence: 99%
“…GitHub is the world's most popular site for storing code [2] and thus is a popular place for software engineering research. Researchers have analyzed GitHub data to see how software engineers track issues [7], [10], [37], resolve bugs [54], use pull requests [61], [66], and even investigate gender bias in open-source projects [57]. Due to GitHub's research popularity, researchers have created tools such as GHTorrent [31] and Boa [13] to assist others, and Google maintains a snapshot of open-source repositories in BigQuery [28], [36].…”
Section: Related Workmentioning
confidence: 99%